THE TYPE OF THE REASONER IN THE 18TH CENTURY RUSSIAN COMEDY - Куликова, Ирина (Literatūra, 2013)
The article deals with the type of the stage reasoner in the 18th century Russian literature. It is a character common for educational comedies in the epoch of the Enlightenment. On the basis of the educational comedies written in the last three decades of the 18th century, the author of the article analyses both the typological features and functions of the reasoner, which were determined by the educational objectives of the Enlightenment theatre. Special attention is given to the analysis of the ethic aspect of the reasoner’s speeches. The focus is put on different reasoning cases of one of the main 18th-century Russian stage reasoner and ideologist Starodum in the comedy “The Simpleton” (Nedorosle) by D. Fonvizin.